2015
DOI: 10.1002/14651858.cd009852.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Muscle energy technique for non-specific low-back pain

Abstract: Background Low-back pain (LBP) is responsible for considerable personal suffering due to pain and reduced function, as well as the societal burden due to costs of health care and lost work productivity. For the vast majority of people with LBP, no specific anatomical cause can be reliably identified. For these people with non-specific LBP there are numerous treatment options, few of which have been shown to be effective in reducing pain and disability. The muscle energy technique (MET) is a treatment technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 35 publications
(2 reference statements)
1
38
1
Order By: Relevance
“…The systematic review of Rubinstein et al [19] also concluded that there is strong evidence suggesting no clinical difference between thrust manipulation and other techniques to reduce pain and improve function in chronic LBP patients. Franke et al [20] also disagreed with our results as they suggested that MET is not effective in LBP. However, they reported that the studies included in their systematic review showed poor quality evidence for this non-significant effect in terms of pain and function.…”
Section: Discussioncontrasting
confidence: 89%
“…The systematic review of Rubinstein et al [19] also concluded that there is strong evidence suggesting no clinical difference between thrust manipulation and other techniques to reduce pain and improve function in chronic LBP patients. Franke et al [20] also disagreed with our results as they suggested that MET is not effective in LBP. However, they reported that the studies included in their systematic review showed poor quality evidence for this non-significant effect in terms of pain and function.…”
Section: Discussioncontrasting
confidence: 89%
“…high energy laser, shock wave or electrostimulation) is not indicated. it is recommended supervised motor therapy, behavioral therapy, massage aimed at normalizing the resting tension of the muscles and improvement of their trophics [26][27][28][29][30][31][32][33][34].…”
Section: Treatmentmentioning
confidence: 99%
“…There is dearth in the literature regarding the effect of MET as an isolated treatment on nonspecific low back pain. It is therefore useful to explore the effectiveness of treatments that may assist people with LBP, particularly those treatments such as MET which are non-invasive and are likely to be safe and inexpensive [6]. The aim is to study the added effect of Muscle Energy Technique in patients having Chronic Nonspecific Low Back Pain for improving functional ability with the hypothesis that there is a good effect of MET in decreasing disability and improving functional ability.…”
Section: Added Effect Of Muscle Energy Technique For Improving Functimentioning
confidence: 99%